THE EFFECT OF EDUCATIONAL BOARDGAME ON STUDENTS' REFLECTIVE THINKING ABILITY IN LEARNING SUBJECT NUTRITION IN FOOD - Al Mustafid, Fika Zakiya; Aristiawan; Cahyani, Vika Puji (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
Reflective thinking skills are one of the five high-level thinking skills in twenty-first-century learning. The process of reflective thinking is crucial, especially in science education. Mastering reflective thinking skills helps students in solving scientific problems using scientific methods. There are three stages of reflective thinking: reaction, elaboration, and contemplation. To enhance students' reflective thinking skills, the first step is to stimulate student interest. One alternative learning model that can engage student interest is Game-Based Learning using educational boardgame. Boardgame is a type of non-digital game that has various advantages compared to other types of games. This study investigated the reflective thinking skills of junior high school students as an impact of using educational game media in science lessons, especially the material of Nutritional Substances in Food. The research was conducted at SMPN 2 Jetis, Ponorogo Regency. The research sample was the VIII grade students of SMPN 2 Jetis. This research is a quantitative study with a research design using a quasi-experiment with a nonequivalent control group. The data collection technique used pre-test and post-test to measure reflective thinking skills before and after treatment in the control class and experimental class. The results showed that reflective thinking skills at the Reaction, Elaboration, and Contemplation stages in the experimental class using boardgame media were not higher than the control class using paper and pencil media. These results can be influenced by several variables that cannot be controlled by researchers. The conclusion of this study showed that boardgame media could not always be used to improve reflective thinking skills.